Patriarki dan Anxiety Pada Ibu yang Memiliki - Putri Rahayu, Restianingsih; Bahriyah, Fitriyani; Putri, Anjeli Ratih Syamlingga; Arlis, Izzawati; Putri, Monifa (Universitas Pahlawan Tuanku Tambusai, 2026)
Mothers are considered a population vulnerable to mental health problems, including anxiety. Within the socio-cultural context of Indonesia, patriarchal systems remain deeply entrenched and may contribute to an increased psychological burden among mothers. This study aimed to examine the relationship between the patriarchal system and maternal anxiety. A quantitative study with an analytic approach was conducted involving 37 mothers. The patriarchal system was examined as the independent variable, while anxiety levels were measured using the Depression Anxiety Stress Scales (DASS-42). Data were analysed using Spearman’s rank correlation. The findings indicated a positive correlation between the patriarchal system and maternal anxiety (r = 0.232), suggesting that higher exposure to patriarchal norms was associated with higher levels of anxiety. However, this association did not reach statistical significance. These findings suggest that patriarchy may represent a psychosocial factor related to maternal anxiety and underscore the importance of considering social support and maternal mental well-being within the family context.